The Impact of Branding, Advertising, and Social Media Marketing on Consumer Purchase Intention, Brand Loyalty, and Brand Equity in the Indonesian Market - Hery Purnomo; Yulia Novita (IPM2KPE, 2024)
This research investigates the influence of branding, advertising and social media marketing on customer purchase intentions, brand loyalty and brand equity in the Indonesian fashion industry. Survey data from 288 Indonesian consumers were analyzed using structural equation modeling (SEM-PLS) to test the relationship between variables. The results of the analysis show that there is a positive and significant correlation between consumer behavior, social media engagement, advertising effectiveness and brand perception. Key findings show that branding, advertising, and social media marketing positively influence brand equity, purchase intention, and brand loyalty. Hypothesis testing demonstrated strong statistical significance, while assessment of the measurement model supported the validity and reliability of the measurement tools used. The structural model developed is able to explain the data adequately, emphasizing the importance of integrated marketing strategies in strengthening the relationship between consumers and brands and improving brand performance in the Indonesian fashion market. The conclusion is that fashion companies can use the insights gained to increase their presence and competitiveness in developing markets such as Indonesia. Keywords: Branding, Advertising, Social Media Marketing, Consumer Behavior